OnabotulinumtoxinA affects cortical recovery period but not occurrence or propagation of cortical spreading depression in rats with compromised blood–brain barrier. Issue 9 (September 2021) - Melo-Carrillo, Agustin; Strassman, Andrew M.; Schain, Aaron J.; Broide, Ron S.; Cai, Brian B.; Rhéaume, Catherine; Brideau-Andersen, Amy D.; Ashina, Sait; Flores-Montanez, Yadira; Brin, Mitchell F.; Burstein, Rami
Abstract : Abstract: OnabotulinumtoxinA (BoNT-A) is an Food and Drug Administration-approved, peripherally acting preventive migraine drug capable of inhibiting meningeal nociceptors. Expanding our view of how else this neurotoxin attenuates the activation of the meningeal nociceptors, we reasoned that if the stimulus that triggers the activation of the nociceptor is lessened, the magnitude and/or duration of the nociceptors' activation could diminish as well. In the current study, we further examine this possibility using electrocorticogram recording techniques, immunohistochemistry, and 2-photon microscopy. We report (1) that scalp (head) but not lumbar (back) injections of BoNT-A shorten the period of profound depression of spontaneous cortical activity that follows a pinprick-induced cortical spreading depression (CSD); (2) that neither scalp nor lumbar injections prevent the induction, occurrence, propagation, or spreading velocity of a single wave of CSD; (3) that cleaved SNAP25—one of the most convincing tools to determine the anatomical targeting of BoNT-A treatment—could easily be detected in pericranial muscles at the injection sites and in nerve fibers of the intracranial dura, but not within any cortical area affected by the CSD; (4) that the absence of cleaved SNAP25 within the cortex and pia is unrelated to whether the blood–brain barrier is intact or compromised; and (5) that BoNT-A does not alter vascular responses to CSD. To the best of our knowledge, this is the first report of peripherally applied BoNT-A's ability to alter a neuronal function along a central nervous system pathway involved in the pathophysiology of migraine. Abstract : Suture-line injections of onabotulinumtoxinA alter a neuronal function along a central nervous system pathway involved in the pathophysiology of migraine that is secondary to appearance of SNAP25 in dural nerve fibers.